Comparative Evaluation of Hardness and Energy Absorption of Some Commercially Available Chairside Silicone-Based Soft Denture Liners and a Heat-Cured Soft Denture Liner - Mutahar M; Al Ahmari NM; Gadah TS; Kariri MAM; Madkhli HY; Somaili DM; Mobarki YMY; Darraj OA; Halawi SM; Al Moaleem MM (Dove Medical Press, 2023)
Mahdi Mutahar,1 Nasser M Al Ahmari,2 Thrya S Gadah,2 Mohammed Ali Mohammed Kariri,3 Hana Y Madkhli,3 Dawood M Somaili,4 Yahya MY Mobarki,5 Omar Ahmed Darraj,6 Sultan M Halawi,7 Mohammed M Al Moaleem8 1Dental Academy, University of Portsmouth, Portsmouth, PO1 2QG, UK; 2Prosthetic Department, College of Dentistry, King Khalid University, Abha, 62529, Saudi Arabia; 3Dental Department, Samtah General Hospital, Ministry of Health, Jazan, Saudi Arabia; 4Dental Department, Dayhamah Primary Health Center, Ministry of Health, Jazan, Saudi Arabia; 5Dental Department, Aldureah Primary Health Center, Ministry of Health, Jazan, Saudi Arabia; 6Dental Department, Algahw Primary Health Center, Ministry of Health, Jazan, Saudi Arabia; 7Dental Department, Al Raha Primary Health Center, Ministry of Health, Jazan, Saudi Arabia; 8Department of Prosthetic Dental Science, College of Dentistry, Jazan University, Jazan, 45142, Saudi ArabiaCorrespondence: Mahdi Mutahar; Mohammed M Al Moaleem, Department of Prosthetic Dental Science, College of Dentistry, Jazan University, Jazan, 45142, Saudi Arabia, Tel +966-550599553, Email mahdi.mutahar@port.ac.uk; malmoaleem@jazanu.edu.saAim: To investigate the hardness and energy absorption of four commercially available chairside types of silicone materials and compare their properties with heat-cured silicone material.Materials: The chairside materials investigated were GC reline soft, mucopren soft, sofreliner soft and elite soft relining. The heat-cured polymer silicone material was Molloplast B. All soft lining materials were processed according to manufacturers' instructions. Two properties were investigated. Ten specimens for each test were prepared for each soft liner except for the water absorption and solubility test, for which only five specimens were prepared. The specimens of energy absorption (10 × 10 × 3 mm) were tested using a Lloyd instruments testing machine. Hardness specimens (38 × 38 × 3) were tested using a shore A durometer and were divided into two subgroups; dry and wet storage.Results: The specimens of energy absorption (10 × 10 × 3 mm) were tested using a Lloyd instruments testing machine. Sofreliner soft was significantly softer than Molloplast B. GC reline soft was significantly harder than molloplast B. At high loads, sofreliner soft and elite soft relining was significantly more resilient than molloplast B. Mucopren soft was significantly stiffer than Molloplast B. At low loads, all materials showed similarities in stiffness and resilience; the difference between them was insignificant. After one month of immersion, GC reline and mucopren significantly increased hardness values.Conclusion: In all conditions and at all four-time points, the hardness values for GC Reline soft were the greatest, and hardness values for Sofreliner Soft were the least. Some chairside soft denture lining materials could have similar significant properties to molloplast-B, such as sofreliner soft and elite.Keywords: complete dentures, denture liners, hardness, polyvinyl siloxane liner, resilience, energy absorption, soft denture lining materials, stiffness